Protective and Blast Resistive Design of Posttensioned Box Girders Using Computational Geometry - Majid Aleyaasin (Advances in Civil Engineering)
The optimal tendon profile and its associated duct geometry for posttensioned box girders are investigated. A computational algorithm has been developed to determine an ideal shape for the tendon and duct. The algorithm is based on a diagonal cross point in the Magnel quadrilateral and uses computational geometry instead of graphical drawing. Thereafter, an ideal parabolic and linear tendon profiles can be calculated from which the covering duct could be shaped. To check the optimality of the results, an automatic examination of Magnel diagrams in various cross sections is incorporated in the algorithm. This enables a unique prestress level to be selected that suits all sections. Then, the mideccentricity of the two crossing points with a common prestress line is chosen as a design eccentricity in each cross section. The optimal duct shape is determined based on such automatic inspections. In a numerical example, the linear, parabolic, and optimal duct geometries are compared and drawn. It is concluded that both linear and parabolic duct shapes can be very close to an optimal shape. In a numerical example, an optimal, box girder with linear open access-type tendons is designed that can withstand extra blast load when explosion occurs.